Libya : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
The cost of energy subsidies is large, and reduces the fiscal space available for public expenditure priorities, including education, health, and infrastructure. Libya's ample hydrocarbon wealth will allow it to reform subsidies while protecting the poor. A gradual phasing out of subsidies would allow adjustment in consumption and minimize the inflationary impact, thereby allowing the social assistance system to be strengthened. After a transfer mechanism is in place to facilitate fuel and electricity subsidy reform, food subsidy reform should be undertaken.